Long-Term Observation and Sequencing Analysis of SKPs-Derived Corneal Endothelial Cell-Like Cells for Treating Corneal Endothelial Dysfunction. (28th May 2021) - Shen, Lin; Sun, Peng; Du, Liqun; Zhu, Jing; Ju, Chengqun; Guo, Hui; Wu, Xinyi
Corneal endothelial dysfunction is a principal cause of visual deficiency. Corneal transplantation is the most effective treatment for corneal endothelial dysfunction. However, a severe shortage of available donor corneas or human corneal endothelial cells (HCECs) remains a global challenge. Previously, we acquired corneal endothelial cell-like cells (CEC-like cells) derived from human skin-derived precursors (SKPs). CEC-like cells were injected into rabbit and monkey corneal endothelial dysfunction models and exerted excellent therapeutic effect. In this study, we prolonged the clinical observation in the monkey experiment for 2 years. Polymerase chain reaction (PCR) and DNA sequencing were carried out to confirm the existence of CEC-like cells. Histological examinations were carried out to show the corneal morphology. Further transcriptome sequencing was also carried out on HCEC, CEC-like cells before transplantation and after transplantation. We found that the monkeys cornea remained transparent and normal thickness. The total endothelial cell density decreased gradually, but tended to be stable and remained in a normal range during 2-year observation. The CEC-like cells persist during observation and could adapt to the microenvironment after transplantation. The gene expression pattern of CEC-like cells was similar to HCEC and changed slightly after transplantation. In conclusion, this study presented a brand-new insight into CEC-like cells and further provided a promising prospect of cell-based therapy for corneal endothelial dysfunction. The renewable cell source, novel derivation method and simple treatment strategy may be clinically applied in regenerative medicine in the future.